Poliovirus and non-polio-enterovirus environmental surveillance in Parma within the “Global Polio Eradication Program” (GPEI) - Zoni, Roberta; Mezzetta, Sandra; Affanni, Paola; Colucci, Maria Eugenia; Fiore, Stefano; Fontana, Stefano; Bracchi, Mariateresa; Capobianco, Emanuela; Veronesi, Licia (Acta Biomedica Atenei Parmensis, 2019)
Background: Environmental surveillance of poliovirus plays an essential role in GPEI both for the detection of WTP and VDPV circulation in endemic areas and for monitoring their absence in polio-free countries. Methods: Since 2005 to 2018, in Parma, 642 wastewater samples were collected from the two wastewater treatment plants and analyzed according to the WHO Guidelines. All isolates supposed being poliovirus were sent to ISS reference laboratory for molecular characterization while NPEV only refer to samples up to 2016. Results: Positivity was obtained in 68% of samples without significant difference between the two treatment plants. Six polioviruses (1.4%) were detected, all characterized as Sabin-like: 4 of them (66.7%) were type 3 and 2 (33.3%) type 1. Coxsackieviruses B mainly recurred among NPEV (85%) while residual 15% was Echoviruses. B4 was the most frequent Coxsackie serotype isolated (31%) while, among Echovirus, Echo 7 and Echo 11 prevail (both 23%). Conclusion: As OPV isn’t used in Italy since 2002, recovery of Sabin-like polioviruses indicates the possibility of poliovirus reintroduction, considering also the important exposure to migratory flows. Finally, monitoring the environmental circulation of NPEV, could compensate for the lack of a surveillance system of the infections they cause.